Lesley Hazleton’s Book "The First Muslim-The Story of Muhammad”: a Critical Review - Muhammad Islam; Khan, Janas (Journal of Islamic and Religious Studies, 2017)
Allah sent his prophets for the guidance of the Human beings. Prophet Muḥammad (SAW) was the last of them. In the short span of only twenty three years, he changed the scenario of the world through the teachings of Islam. Apart from countless Muslims, the Non Muslim scholars also wrote about his life. Lesley Hazleton is a Non Muslims scholar wrote "The First Muslim-The Story of Muhammad". This book is divided into three parts; 1 The Orphan, 2 Exile & 3 The Leader. She expressed her views about the Prophet in her book openly. Many times she praises the prophet (SAW) for his achievements but like her successors, she criticizes his life. Sometimes she criticizes the family (forefathers) of the prophet, sometimes, in soft words criticizes the family life and polygamy of the Prophet (SAW). This research paper discusses her approach to the life of the Prophet (Seerah) in the light of her book.